Digitalizing Government Services Through the Paspas Permit Implementation Towards A Citizen-Centered Public Service Operation in Valenzuela City - Pajenado, Rex S.; Rivera, Michville A. (Future Science / FSH-PH Publications, 2025)
The increasing digitalization of public services has driven govern-ments to integrate information and communication technology (ICT) into governance. In the Philippines, despite efforts to enhance e- gov-ernance, bureaucratic inefficiencies continue to hinder progress. The Paspas Permit system launched in Valenzuela City in 2019, aims to streamline business permit transactions, reducing processing time and promoting transparency. This study evaluates the implementa-tion, performance, and user adoption of the system, employing a mixed-method research design that combines quantitative surveys and qualitative interviews. Findings indicate that while Paspas Permit improves efficiency, adoption remains low due to digital literacy gaps, system complexity, and lack of awareness. While many users appreci-ate its convenience, some prefer traditional methods, citing trust and usability concerns. The study underscores the need for enhanced user engagement, continuous system improvements, and targeted promo-tion strategies to increase adoption and retention. Insights from this research contribute to e-governance policy discussions and provide recommendations for optimizing digital service delivery in local gov-ernment units.